2019
DOI: 10.3389/fmars.2019.00647
|View full text |Cite
|
Sign up to set email alerts
|

Managing the Effects of Noise From Ship Traffic, Seismic Surveying and Construction on Marine Mammals in Antarctica

Abstract: Erbe et al. Antarctic Underwater Noise score was a refinement of noise exposure criteria. Environmental evaluations are a requirement before conducting activities in the Antarctic. Because of a lack of scientific data on impacts, requirements and noise thresholds often vary between countries that conduct these evaluations, leading to different standards across countries. Addressing the identified research needs will help to implement informed and reasonable thresholds for noise production in the Antarctic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 187 publications
(170 reference statements)
0
21
0
Order By: Relevance
“…The first of its kind in international waters, it was established in 2016 by the Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR) following scientific advice [99]. Human presence in the Antarctic is increasing with an almost exponential increase in the annual number of visitors over the last two decades raising concerns about potential impacts on the Antarctic ecosystem [100]. Monitoring is needed to inform management of resources, determine the health of the ecosystem and assess whether the RSRMPA is achieving the objectives for which it was established.…”
Section: Application To Conservation Managementmentioning
confidence: 99%
“…The first of its kind in international waters, it was established in 2016 by the Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR) following scientific advice [99]. Human presence in the Antarctic is increasing with an almost exponential increase in the annual number of visitors over the last two decades raising concerns about potential impacts on the Antarctic ecosystem [100]. Monitoring is needed to inform management of resources, determine the health of the ecosystem and assess whether the RSRMPA is achieving the objectives for which it was established.…”
Section: Application To Conservation Managementmentioning
confidence: 99%
“…We have shown that accurate models of the Australian marine soundscape must include biological sources (i.e., primarily whales and fishes). Natural biological and physical noise ought to be considered in management frameworks to provide context (e.g., for noise management in the Southern Ocean [79]).…”
Section: Discussionmentioning
confidence: 99%
“…Antarctica is predominantly governed by high-income countries, and thus might be expected to receive higher levels of research attention. Ship noise, in particular, is rapidly increasing off Antarctica due to booming tourism and heightened fisheries effort (Erbe et al, 2019). While Arctic marine mammals were first studied several decades ago, at a time when industrial development (i.e., mostly offshore oil and gas) was expected to grow rapidly, no such impetus has yielded a research increase in Antarctica.…”
Section: Geographic Areamentioning
confidence: 99%